Cochrane Database of Systematic Reviews 2014
DOI: 10.1002/14651858.cd011298.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for improving postpartum contraceptive use: evidence from non-randomized studies

Abstract: We considered the quality of evidence to be very low. The studies had limitations in design, analysis, or reporting. Three did not adjust for potential confounding and only two had sufficient information on intervention fidelity. Outcomes were self reported and definitions varied for contraceptive use. All studies had adequate follow-up periods but most had high losses, as often occurs in contraception studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
2
13
0
4
Order By: Relevance
“…Second, the rate of expulsion was low (8%) and consistent with or lower than expulsion rates reported in other published studies, 10 , 23 - 25 indicating a high standard of insertion technique among the trained providers in this study. While expulsion rates with post-placental IUD insertion appear to be higher than with interval insertion, studies have concluded that immediate postpartum IUD insertion is safe and effective and the benefits outweigh the disadvantage of the increased risk of expulsion, 7 particularly in settings with limited access to health services.…”
Section: Discussionsupporting
confidence: 90%
“…Second, the rate of expulsion was low (8%) and consistent with or lower than expulsion rates reported in other published studies, 10 , 23 - 25 indicating a high standard of insertion technique among the trained providers in this study. While expulsion rates with post-placental IUD insertion appear to be higher than with interval insertion, studies have concluded that immediate postpartum IUD insertion is safe and effective and the benefits outweigh the disadvantage of the increased risk of expulsion, 7 particularly in settings with limited access to health services.…”
Section: Discussionsupporting
confidence: 90%
“…In the Meta analysis of six studies, the Cochrane data group 16 found that intervention with educational strategies are associated with significantly higher use of modern methods of contraception. In our study we observed that the most popular source of information for contraception was social network of friends, neighbors and relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Male partners can have a significant impact on women's access to SRH education and services. Yet existing interventions mainly focus on women [107][108][109]. We recommend future interventions make efforts to involve male partners, with emphasis on empowering women to take charge of their own reproductive health.…”
Section: Policy and Research Implicationsmentioning
confidence: 99%